Congenital Cytomegalovirus Hepatitis in the XXI Century is not Uncommon! - N.P. Skorodumova; T.I. Kovalenko; Ye.V. Shvedkaya; Ye.V. Khmara (Zaslavsky O.Yu., 2014)
The article presents features of early clinical and laboratory diagnosis of congenital cytomegalovirus (CMV) hepatitis. The analysis of the causes of late diagnosis of chronic hepatitis is carried out. Some children have repeatedly appealed to the doctor and treated for gastroduodenitis, cholecystitis, biliary dyskinesia, ulcerative colitis. Chart review allowed to assume that the extrahepatic manifestations of chronic hepatitis and liver cirrhosis district pediatricians interpreted as allergy (recurrent urticaria), juvenile rheumatoid arthritis (arthritis), vegetovascular dystonia (ECG changes); endocrine violations (delayed menstruation, striae on the abdominal skin) - as the feature of puberty; signs of hypo- or hyperthyroidism - as endemic pathology. A sequence of doctor's actions in diagnosing congenital CMV infection, mainly affecting the liver, is provided.